Variability within the human iNOS gene and Achilles tendon injuries: Evidence for a heterozygous advantage effect. Issue 4 (April 2020) - Brookes, Charlotte; Ribbans, William J.; El Khoury, Louis Y.; Raleigh, Stuart M.
Abstract: Objectives: The aim of this case control genetic association study was to explore whether two variants within the inducible nitric oxide synthase ( iNOS ) gene, rs2779249 (C/A) and rs2248814 (A/G), influenced the risk of Achilles tendinopathy in a British population. Design: Candidate gene, case control association study. Method: We recruited 145 individuals diagnosed with Achilles tendon pathology and 132 asymptomatic controls. All participants were genotyped for the iNOS variants using qPCR and significant associations were discovered using a combination of Chi squared and ANOVA type analysis. Results: The CA genotype of the iNOS rs2779249 variant was protective and conformed to a heterozygous advantage model of inheritance as it was overrepresented in the control participants (p = 0.009). In sex specific analysis the protective association persisted in male participants (p = 0.016) but not in females. Unlike the rs2779249 variant, the rs2248814 variant was not associated with Achilles tendinopathy or Achilles tendon rupture. Conclusion: The rs2779249 CA genotype within the human iNOS gene appears to protect individuals from Achilles tendinopathy. This study further supports a genetic contribution to modifying the risk of Achilles tendon problems. The study also infers an important role for nitric oxide in tendon healing and/or degradation.